SELECTION OUTSTANDING STUDENT USING MOORA METHOD - Ichsan; Pandu Adi Cakranegara; Desty Endrawati Subroto; Yunita Dwi Wikandari; Ahmad Jurnaidi Wahidin (Sean Institute, 2022)
In multi-criteria decision making, choosing the preferred alternative from among numerous alternatives is a classic challenge; approaches are required to provide decisions that are impartial. In this study, the Average Report Card Value (C1), Attitude Scores (C2), Attendance Scores (C3), Achievements (C4), and Extracurriculars (C5) were used to address the issue of outstanding student. To find the best alternative decisions for pupils who excel, 5 additional samples of students were chosen. For the purpose of resolving complicated mathematical issues arising from several opposing criteria qualities, the Multi-Objective Optimization on The Basic of Ratio Analysist (MOORA) method was selected. The results showed that alternative A4, which had a score of 0.49024595 and was the best alternative for excellent students, had the alternative ranking of outstanding students with the highest score.